The Influence of Entrepreneurial Communities and Government of UMKM in Medan City - Gita Dewi Winardi; Ernita; Mustika Dewi (urn:multiple://2988-7828multiple.v3i110)
The purpose of this study was to determine the influence of the entrepreneur community and government support on the development of UMKM in Medan City, both partially and simultaneously. The pre-survey results identified several problems related to UMKM development and highlighted two key influencing factors: the entrepreneur community and government support. The study population consisted of UMKM players in Medan City who are members of the entrepreneur community and have received government support. The sample was selected using the Lemeshow formula, resulting in 100 respondents. Data were collected through questionnaires to capture respondents perspectives on the independent variables: the entrepreneur community and government support. A quantitative research method was employed. The analysis included descriptive statistics, simple linear regression, and significance testing using t-tests, f-tests, and the coefficient of determination (R²) with SPSS version 26. The results indicate that both the entrepreneur community and government support have a positive and significant effect on the development of UMKM in Medan City, both independently and simultaneously.